Persistence of Politicians and Firms'Innovation - Giorgio Bellettini; Carlotta Berti Ceroni; Giovanni Prarolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
We empirically investigate whether the persistence of politicians in political institutions affects the innovation activity of firms. We use 12,000 firm-level observations from three waves of the Italian Observatory over Small and Medium Enterprises, and introduce a measure of political persistence defined as the average length of individual political careers in political institutions of Italian municipalities. Standard OLS shows no raw correlation between political persistence and firms' innovation activity. However, once the causal effect is isolated by means of instrumental variables, using death of politicians as an exogenous source of variation of political persistence, we find a robust negative relation between political persistence and the probability of process innovation. This finding is consistent with the view that political stability may hinder firms' incentive to innovate to maintain their competitiveness, as long as they can extract rents from long-term connections with politicians.
Keywords: D22; D72; O31; 330